Are clownfish groups composed of close relatives? An analysis of microsatellite DNA variation in Amphiprion percula - BUSTON, PETER M; BOGDANOWICZ, STEVEN M; WONG, ALEX; HARRISON, RICHARD G (Molecular ecology, 2007)
A central question of evolutionary ecology is: why do animals live in groups? Answering this question requires that the costs and benefits of group living are measured from the perspective of each individual in the group. This, in turn, requires that the group's genetic structure is elucidated, because genetic relatedness can modulate the individuals' costs and benefits. The clown anemonefish, Amphiprion percula, lives in groups composed of a breeding pair and zero to four nonbreeders. Both breeders and nonbreeders stand to gain by associating with relatives: breeders might prefer to tolerate nonbreeders that are relatives because there is little chance that relatives will survive to breed elsewhere; nonbreeders might prefer to associate with breeders that are relatives because of the potential to accrue indirect genetic benefits by enhancing anemone and, consequently, breeder fitness. Given the potential benefits of associating with relatives, we use microsatellite loci to investigate whether or not individuals within groups of A. percula are related. We develop seven polymorphic microsatellite loci, with a number of alleles (range 2-24) and an observed level of heterozygosity (mean = 0.5936) sufficient to assess fine-scale genetic structure. The mean coefficient of relatedness among group members is 0.00 ± 0.10 (n = 9 groups), and there are no surprising patterns in the distribution of pairwise relatedness. We conclude that A. percula live in groups of unrelated individuals. This study lays the foundation for further investigations of behavioural, population and community ecology of anemonefishes which are emerging as model systems for evolutionary ecology in the marine environment.